The Late Cretaceous alkaline magmatism in the SE Brazilian coast: new paleomagnetic data and age constraints - Marcia Ernesto; Maria Irene Bartolomeu Raposo (Brazilian Journal of Geology, 2023)
Abstract Alkaline dikes from the Santos-Rio de Janeiro coast, SE Brazil, mainly from São Sebastião and Búzios islands, yielded a Late Cretaceous paleomagnetic pole (SR) located at 319.7°E 81.2°S (N = 44, A95 = 3.0°, k = 44). This pole includes some sites of alkaline stocks from São Sebastião Island of the same age and supersedes the previous pole for this island. To match the available radiometric ages and the prevailing normal polarity remanence of the rocks with the geomagnetic polarity time scale, the SR pole is placed at 84 Myr. Another group of alkaline rocks, dikes located mainly in Rio de Janeiro, was assigned an age of less than 70 Myr. The ages of the Poços de Caldas, Itatiaia, and Passa Quatro paleomagnetic poles are also discussed based on available radiometric data. Assuming a rigid plate, the SR pole indicates the southward movement of about 7° with virtually no rotation between 100 and 84 Myr. From approximately 84 to 70 Myr, a clockwise rotation of 8° is postulated, with slight variation in latitude.